The Cambridge history of American women's literature - Bauer, Dale M. (C.U.P, 2012)
"The field of American women's writing is one characterized by innovation: scholars are discovering new authors and works, as well as new ways of historicizing this literature, rethinking contexts, categories, and juxtapositions. Now, after three decades of scholarly investigation and innovation, the rich complexity and diversity of American literature written by women can be seen with a new coherence and subtlety. Dedicated to this expanding heterogeneity, The Cambridge History of American Women's Literature develops and challenges historical, cultural, theoretical, even polemical methods, all of which will advance the future study of American women writers - from Native Americans to postmodern communities, from individual careers to communities of writers and readers. This volume immerses readers in a new dialogue about the range and depth of women's literature in the United States and allows them to trace the ever-evolving shape of the field"--